Adolescent Violence Towards Parents: Another Type of Intrafamily Violence - Roni Eshaq Bakos Shukri; Zbigniew Formella (The Francis de Sales Scientific Society (TNFS.PL), 2022)
Family violence in its various forms is contrary to the violence that occurs in public environments; these forms of aggressive behavior occurring at home make it easier for perpetrators to hide their aggression and, at the same time, make it more difficult for the victims to draw attention to their condition. They are, moreover, particularly traumatic because they cause loss of confidence between family members. According to Holt there are five different forms of domestic or family violence that have emerged as social problems over the past 50 year of the last century: 1) child abuse, 2) intimate partner abuse also known as family or domestic violence, 3) elder abuse, 4) sibling abuse and 5) parent abuse, which has not yet achieved the status of "social problem". In fact, early research in the field of family violence focused primarily on spousal violence and child abuse, but it neglected the phenomenon of violence of children against their parents. The main aim of this article is to explore adolescent violence towards parents as a "new and emerging" form of intrafamily violence, which is a subject of increasing interest of researchers and professionals.